Pressure pain thresholds of upper limb peripheral nerve trunks in asymptomatic subjects. - Sterling M; Treleaven J; Edwards S; Jull G (Physiotherapy Research International, 2000)
BACKGROUND AND PURPOSE: Palpation of peripheral nerve trunks has been advocated as a method of assessing the presence of hyperalgesic nerve tissue as a contributing factor to pain syndromes in musculoskeletal disorders of the upper quadrant. This study investigated, in the first instance, the pressure pain thresholds of the median, radial and ulnar nerve trunks of the upper limb in healthy, asymptomatic subjects. METHOD: Forty-five male and 50 female healthy volunteer subjects participated in this study which involved measurement of pressure pain thresholds by use of pressure algometry bilaterally over the three peripheral nerve trunks in the upper limbs. RESULTS: Pressure pain thresholds were shown to be lowest in the median nerve (p = 0.001) and lower in female subjects (p = 0.001). Laterality (p = 0.077) or the age of the subject (p = 0.254) did not significantly influence results. CONCLUSIONS: The study demonstrated differences in pressure pain thresholds in the three nerve trunks of the upper limb. These findings should be taken into account when interpreting the findings of nerve palpation in musculoskeletal upper quadrant disorders.